Carriage of methicillin-resistant Staphylococcus aureus in veterinary personnel - Zemlicková, H; Fridrichová, M; Tyllová, K; Jakubů, V; Machová, I (Epidemiology and infection, 2009)
A survey of 280 attendees at a veterinary meeting in the Czech Republic in 2008 revealed a carriage rate of 0.7% for methicillin-resistant Staphylococcus aureus (MRSA). The two strains isolated were of distinct genetic lineages, carried type IV SCCmec determinants and were negative for Panton-Valentine leukocidin genes. The MRSA positivity rates for veterinarians in the Czech Republic is considerably lower than reported elsewhere.
Keywords: leukocidiny; dospělí; Genotype; proteiny vázající penicilin; Female; Prevalence; exotoxiny; Adult; Penicillin-Binding Proteins; ženské pohlaví; mladý dospělý; Bacterial Toxins; Animal Technicians; bakteriální proteiny; Bacterial Proteins; Carrier State; lidé; surveillance populace; genotyp; veterináři; methicilin rezistentní Staphylococcus aureus; Exotoxins; Leukocidins; prevalence; přenašečství; Male; Aged; Czech Republic; Young Adult; Population Surveillance; bakteriální toxiny; Česká republika; lidé středního věku; senioři; veterinární technici; mužské pohlaví; Veterinarians; Middle Aged; Methicillin-Resistant Staphylococcus aureus; Humans